Multimodal geothermal exploration in the Lesser Antilles Arc at the Lamentin lowland (Martinique). (March 2019) - Gadalia, A; Bouchot, V; Calcagno, P; Caritg, S; Courrioux, G; Darnet, M; Jacob, T; Labeau, Y; Taïlamé, A L; Terrier, M; Thinon, I; Vittecoq, B
Abstract: The aim of the last geothermal exploration campaign at the Lamentin lowland (Martinique) was to specify the characteristics and the extent of the local geothermal system. In this purpose, previous data were re-processed and new field data were acquired through geological, gravimetric, electromagnetic (CSEM and TEM) and fluids geochemical surveys. All the collected data were gathered in a 3D geological model leading to a new conceptual model. The Lamentin lowland is considered as an active graben controlled by major NW-SE faults and crossed by a NE-SW accommodating fault system. Recent, restricted and monogenic hydro-volcanism was highlighted, associated to large hydrothermal deposits from a first high temperature (HT) geothermal episode. Associated with thermal and soil gas anomalies and CO2 -rich springs, they mark out the main faults. A shallow, thin and very conductive layer (<10 Qm) was mapped by CSEM and TEM, as the caprock of the previous HT geothermal system. Current geothermal fluid results from the mixing of 25-30% of seawater with fresh water flowing likely from the northern relief where annual precipitation exceeds 4 m. It is then heated to 115 ± 25°C and flows in a convective ascent through the major NW-SE fault. Northern Lamentin lowland appears to be a fault-limited and shallow medium enthalpy geothermal system.